1981
DOI: 10.1002/kin.550130105
|View full text |Cite
|
Sign up to set email alerts
|

A study of the reactions of fluorine with hydrogen and methane in the initiation phase using a miniature tubular reactor

Abstract: A small tubular reactor having an inner diameter of 1-2 mm and used as the source in a molecular beam apparatus is described in detail. This arrangement allows the study of fast reactions with reaction times smaller than 1 msec. The preexplosive reaction phase between Fz and Hz and CHI, respectively, is investigated to find out the initiation reactions. In the Fz/H2 reaction, initiation is brought about by heterogeneous generation of F atoms or some other surface reaction. Evidence is also obtained for chain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Therefore, the reaction is not responsible for the chain-branching step in the H 2 /F 2 /O 2 /N 2 flame, and the upper bound of its rate constant was determined to be ∼10 –13 cm 3 s –1 . This upper bound is smaller by a factor of ∼10 2 than the value of the rate constant employed by Warnatz et al , in their kinetic modeling studies of the H 2 /F 2 /Ar flame; however, the value is consistent with those obtained in the studies of Sullivan et al and Seeger et al, who suggested the values of k 1 = (3–12) × 10 –18 cm 3 s –1 at 350 K and k 1 < 1.7 × 10 –13 cm 3 s –1 at ∼400 K, respectively.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, the reaction is not responsible for the chain-branching step in the H 2 /F 2 /O 2 /N 2 flame, and the upper bound of its rate constant was determined to be ∼10 –13 cm 3 s –1 . This upper bound is smaller by a factor of ∼10 2 than the value of the rate constant employed by Warnatz et al , in their kinetic modeling studies of the H 2 /F 2 /Ar flame; however, the value is consistent with those obtained in the studies of Sullivan et al and Seeger et al, who suggested the values of k 1 = (3–12) × 10 –18 cm 3 s –1 at 350 K and k 1 < 1.7 × 10 –13 cm 3 s –1 at ∼400 K, respectively.…”
Section: Resultssupporting
confidence: 81%
“…The mixtures of H 2 and F 2 are known to explode spontaneously, and their explosion limits have been studied in the 1960–70s. The kinetic behavior of H 2 /F 2 mixtures has also been examined in flow reactors. These studies indicated rapid reactions of H 2 /F 2 mixtures even at room temperature due to the chain reaction mechanism outlined below. They also suggested inhibition of the reactions and explosions upon addition of a small amount of O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen abstraction by F is also fast and efficient. An informative comparison of the rates of hydrogen abstraction from n ‐butane for various active species is given in Table 3 29–32. A more detailed analysis of hydrogen abstraction is included in Part 2 of this paper 11…”
Section: Resultsmentioning
confidence: 99%
“…The database of rate constants for fluorine transfer is even more sparse than that for iodine transfer and tends to rely on more specialized methods. It is summarized in Table . ,,,− …”
Section: Introductionmentioning
confidence: 99%
“…For methyl, pulsed laser photolysis of F 2 in the presence of methane and time-resolved detection of the IR emission from vibrationally excited HF allowed the extraction of both the rate constants for hydrogen and fluorine transfer ( 1a″′ ) . Study of the pre-explosive phase of CH 4 –F 2 mixtures at 300–400 K in a small tubular reactor functioning as the source in a molecular beam apparatus with mass spectroscopic detection gave the composite quantities A o A F and E o + E F , where reaction “o” is the proposed initiation step: CH 4 + F 2 → CH 3 • + HF + F • . These were deconvoluted by a computer fit of the data to give the quite similar value 1b″′ .…”
Section: Introductionmentioning
confidence: 99%